PEMANFAATAN CITRA LANDSAT 8 UNTUK ANALISIS INDEKS VEGETASI DI DKI JAKARTA - Siti Novianti Lufilah; Afra DN Makalew; Bambang Sulistyantara (Jurnal Lanskap Indonesia, 2017)
In Article 28 of Law No. 26 Year 2007 on Spatial Planning, plan of providing and utilization of green open space are included in the spatial planning aspects of the city, where the extent of at least 30% of the area of a city. Jakarta which has a total land area of 66.233 hektare achieve, there are currently only 14,94% of the total extent of which is open space. In support of green open space program, it would require the calculation of the land area of green space appropriately, so that the remote sensing data are increasingly being used to measure green open space. This article presents a study on the utilization of Landsat 8 to analyze the vegetation index using the Normalized Difference Vegetation Index (NDVI). NDVI employs the Multi-Spectral Remote Sensing data technique to find vegetation index, land cover classification, vegetation, water bodies, open area, scrub area, hilly areas, agricultural area, thick forest, thin forest with few band combinations of the remote sensed data. Remote sensing, especially Landsat 8 and geographic information systems (GIS) are used to obtain information about the appearance on the earth surface. From the empirical study, the class of sparse vegetation ranged from 0.1795–0.3172 (37.29% of vegetation area; 12,03% of Jakarta area), the class of medium vegetation ranged from 0.3173–0.4110 (25.36% of vegetation area; 8,18% og Jakarta area), and class of heavy vegetation ranged from 0.4111–0.7086 (37.35% of vegetation area; 12,05% of Jakarta area). The rest of the area instead of vegetation about 67,4% of Jakarta area.Keywords: geographic information systems (GIS), green open space, Jakarta, Landsat 8, NDVI